A new epiphytic species of Gastrochilus (Orchidaceae: Epidendroideae) from Yunnan, China - Rao, Wen-Hui; Liu, Zhong-Jian; Zhang, Guo-Qiang; Chen, Xu-Hui; Huang, Jie; Chen, Gui-Zhen; Chen, Li-Jun (Phytotaxa, 2019)
Gastrochilus Don (1825: 32.), subtribe Aeridinae (Orchidaceae), includes about 50 species, distributed from Southeast Asia to the Himalayas (Lucksom 2003, Jin et al. 2007, Shakya & Shrestha 2007, Chen et al. 2009). Generally, it is characterized by a saccate hypochile and two porate pollinia (Tsi et al. 1999). In China, about 30 species are found according to the most recent revision and recently published new species (Chen et al. 2009, Yi et al. 2010, Liu et al. 2016, Liu & Gao 2018).